ANALISA DAN SIMULASI PENENTUAN RUTE PADA APLIKASI NAVIGASI KENDARAAN BERMOTOR DI KOTA MAKASSAR - Tandungan, Levi Oktavian (Fakultas Teknologi Informasi, Universitas Atma Jaya Makassar, 2020)
In recent years, living standards in Indonesia have begun to increase and the desire for people to buy vehicles continues to increase. This encourages the growth of the number of motor vehicles to continue to increase rapidly. According to the latest data taken in June 2017, the number of vehicles in the city of Makassar is 1,425,635. When compared with a decade earlier the growth in the number of vehicles had increased by more than one hundred percent, which in 2007 the number of vehicles was 613,315. The growth in the number of vehicles is also driving congestion and air pollution. Congestion itself can hamper the economy because it can hamper the production and distribution process, Smart City is a concept that is offered especially in traffic-related problems such as the nearest route information to avoid congestion. One technology that can be applied in Smart City infrastructure is a wireless sensor network. The application of the wireless sensor network itself forms a network formed by a number of Arduino sensor nodes where each sensor node detects physical phenomena that occur at that node. Against the results of the sensor node accumulation is simulated with the weight of the distance of the road. The accumulation results are processed using the Dijkstra algorithm and the Floyd-Warshall algorithm and then an analysis of the simulation results is performed. Research analysis and simulation of motor vehicle navigation applications in the city of Makassar produces a route from each algorithm to a simulation of traffic conditions and also analyzes the results of the two algorithms from the selection of the lane and the speed of determining the lane.